Analysis of the true and fair view concept: an Islamic perspective - Salihin, Abang; Abdul Hamid, Fatima; Abdulrahman Anam , Ousama (Inderscience Enterprises Ltd, 2015)
The aim of this paper is to critically examine the applicability of the concept of ‘True and Fair View’ (TFV) from an Islamic perspective. It then explores the position and roles of TFV in the Islamic accounting context. The sources of data consist of the shari’ah fundamentals from the Islamic legal sources, in addition to relevant accounting standards and regulations. The paper found that the TFV concept is not contrary to Islamic shari’ah and that TFV plays certain roles in Islamic accounting. Thus, the paper suggests that the Islamic standard setters retain the term as it is not against Islamic shari’ah and it will help avoid confusion among users of financial statements. With this, the TFV concept should continue to be used in Islamic accounting until a more appropriate phrase is coined. The paper can be considered among the first papers that analyse the TFV concept from an Islamic perspective.